Deployment of teachers in the plantation sector and its impact on quality of education - Ramathass, P. (International Journal of Psychosocial Rehabilitation, 2020)
This research deals with the “Teacher deployment in Difficult Area Schools” is aimed at identifying the amount of influence that the physical and social environment of the schools in the difficult areas, the access for the professional development of teachers and the administrative procedures have on the teacher deployment in these areas. From 108 Tamil medium schools in the Hatton Education Zone of the Nuwara – Eliya District principals of 22 and 283 teachers were selected for this research. In addition, Directors of Education and representatives of Trade Unions of Teacher Transfer Board were also included. The samples were selected using the Disproportionate Stratify Random sampling method. The principals and teachers were given structured and open questioners. The questions included factors that were identified in the literature review as influencing the Teacher Deployment. The responses were graded giving marks from 1 to 5 according to Likert’s Scale of 1 to 5. In addition the Directors of Education were interviewed and the representatives of Teachers Trade Unions participated focused group discussion. Further data were collected through observation data sheet as well. Thus, this research took the form of a Mix Mode Research Method. The data collected were analyzed using weighted score technique. The analysis of the data reviewed those physical and social factors in relation to the school environment, Professional Development and the Deployment procedures have an impact on teacher deployment in the difficult area schools of plantation sector. These findings match up with the findings of the other researches on Teacher deployment. Therefore the working conditions of Teachers and the environment must be improved in order to improve Teacher deployment in difficult area like plantation sector.